Xin Su Ning—A Review of Basic and Clinical Pharmacology Integrated With Traditional Chinese Medicine Antiarrhythmic Theory - Wang, Xuan; Wang, Taiyi; Ding, Shuwen; Ma, Yu-Ling (Frontiers in Pharmacology, 2021)
Xing Su Ning (XSN) is a patented multicomponent medicine, which was certified in 2005 by China State Food and Drug Administration to produce pharmaceutically and to be used clinically. XSN capsule was developed from an effective formula composed by Prof. Shuwen Ding of Shandong University of Traditional Chinese Medicine. Through more than 30 years of clinical observation, Prof. Ding concluded that XSN has a significant effect on arrhythmia with Tan-Re-Rao-Xin Syndrome according to Traditional Chinese Medicine (TCM) diagnosis. XSN, derived from a classical TCM formula Huanglian Wen Dan Decoction, is formulated with 11 Chinese herbal medicine to treat cardiac ventricular arrhythmia. Clinical evidence suggests it is particularly efficacious for the arrhythmias induced by cardiac ischemia and viral myocarditis without obvious adverse reactions being reported. Cellular electrophysiological studies in ventricular myocytes revealed that XSN prolongs the duration and suppresses the amplitude of the action potential (AP), which are supported by the blockage of sodium and potassium channels indicating the characteristics of class I & III antiarrhythmic drugs. A recently reported double-blind, placebo-controlled multicenter clinical trial of XSN, enrolled 861 patients (ChiCTR-TRC-14004180), showed that XSN significantly inhibited premature ventricular contraction (PVC). The cellular electrophysiological discoveries provided the mechanistic evidence for the clinical efficacy on inhibition of PVC by XSN as demonstrated in the clinical trial. These studies for the first time, provided exclusive evidence that multicomponent TCM antiarrhythmic medicine can be evaluated with conventional research methods that have been used for antiarrhythmic drug discoveries for decades. We aimed to give a comprehensive review on XSN including its origin with the support of TCM theory, its pre-licensing clinical use and development, and its pharmacological and clinical study discoveries. The review will be summarized with the discoveries reported in a novel network pharmacological study that introduced a weight coefficient, which made it possible to evaluate the pharmacological properties of TCM formula with regard to its formation based on TCM theory. We hope the advances in how XSN was studied may offer useful guidance on how other TCM could be studied with respect of the integrity of the TCM formulas.